Factors associated with the understanding of nutritional labels reported by consumers in a city in the interior of Sao Paulo - Santos, Ellen R.; Corrente, Jose Eduardo [UNESP]; Fumes-Ghantous, Giovana (Univ Federal Alfenas, 2023)
The nutritional labels help people to do choices about their products. This study evaluated the factors associated to the ease comprehension of nutritional labels related by consumers in a countryside city of Sao Paulo state, Brazil. A questionnaire was answered by 100 consumers of a supermarket chain, through which sociodemographic variables and information about labels were collected. For sample characterization, tables with percentage values were used; chi-square tests were performed to verify the association between the variables studied and the ease of understanding of the contents contained in the labels, and a logistic regression model was proposed. The factors that showed significant associations with the understanding of the contents on the labels were gender, age, education level and previous knowledge to their information (p<0.05). According to the logistic model, corrected by age, to assess the ease of understanding the labels, it was found that men were more likely to understand their contents than women (OR (CI 95%): 0.284 (0.092-0.876)), as well as those people who already had some previous education on the subjects described in them (OR (CI 95%): 0.106(0.029-0.390)). People with more education reported having more problems to understand the information (OR (CI 95%): 3.572(1.257-10.152)). It was concluded that gender, age group, education level and to have accessing to prior information about labels affect the understanding of their contents; and detailed and more accessible label is desirable.
Keywords: logistic regression; labeling; association tests